Effect of Teacher-Pupil Ratio on Academic Performance of Pupils in Selected Primary Schools in Kabale Municipality. - Turyahabwe, Frank (Kabale University, 2024)
The study was about the effect of teacher-pupils ratio on Pupils' academic performance in primary schools in Kabale Municipality. The study was guided by three objectives which were: to find out the teacher; pupil ratio in primary schools in Kabale municipality, to find out the factors affecting the academic performance of pupils in primary schools in Kabale Municipality, to establish the effect of teacher-pupil ratio on the academic performance of pupils in primary schools in Kabale municipality. A targeted population of 103 respondents was considered for the study. These included the pupils, teachers, and head teachers. Both simple random and purposive sampling techniques were used in identifying the study sample size. The methods that were used in data collection included questionnaires, observation, and interviews. Data collected was edited, coded, entered into the computer, and analyzed with Excel, a Microsoft statistical package, the results were presented in tables. The study showed the factors affecting the academic performance of pupils in primary schools in Kabale Municipality and these included performance Pressure accounting 18(17.4%), family Background by 19(18.4%), learning Infrastructure by 25(24.2%), difficulty in Understanding accounted 14(13.5), teacher-Student Ratio by 22(21.3%). The study findings on how the teacher-pupil ratio influences academic performance in primary included student Engagement accounted 18(17.8%), classroom management by 15 (14.5%), resource allocation by 17(16.5%), and timely feedback by 11(10.6%). The study further found that the effect of teacher-pupil ratio on the academic performance of pupils in primary schools as classes of 20 pupils or less accounted for 18(17.4%), reduced repetition and dropouts Small class sizes narrowed the achievement gap (17.5%), quality of education is much better when pupil-teacher ratio is low by 12(11.6%). The study further concluded that the teacher-pupil ratio is low and affects the academic performance of pupils in primary schools in Kabale municipality.. The study recommends that further studies should be carried out on the other factors affecting the academic performance of pupils.